Folic acid modified gelatine coated quantum dots as potential reagents for in vitro cancer diagnostics. - GOUNKO, IOURI; GERARD, VALERIE; MAGUIRE, CIARAN (My University, 2011)
BACKGROUND: Gelatine coating was previously shown to effectively reduce the cytotoxicity of CdTe Quantum Dots (QDs) which was a first step towards utilising them for biomedical applications. To be useful they also need to be target-specific which can be achieved by conjugating them with Folic Acid (FA). RESULTS: The modification of QDs with FA via an original "one-pot" synthetic route was proved successful by a range of characterisation techniques including UV-visible absorption spectroscopy, Photoluminescence (PL) emission spectroscopy, fluorescence life-time measurements, Transmission Electron Microscopy (TEM) and Dynamic Light Scattering (DLS). The resulting nanocomposites were tested in Caco-2 cell cultures which over-express FA receptors. The presence of FA on the surface of QDs significantly improved the uptake by targeted cells. CONCLUSIONS: The modification with folic acid enabled to achieve a significant cellular uptake and cytotoxicity towards a selected cancer cell lines (Caco-2) of gelatine-coated TGA-CdTe quantum dots, which demonstrated good potential for in vitro cancer diagnostics.
PUBLISHED
Keywords: Oncology; Biochemistry; Quantum Dots; Folic acid; bio-imaging; Cancer